Sangeetha Pulapaka
0

Step 1 : Recall what is elimination method

https://www.qalaxia.com/viewDiscussion?messageId=5cd64bc1ab5a2834360299d0

Step 2: Solve the system of linear equations by elimination

We cancel out the x term

------------------------------

   8y - 2y = -24 -12

Subtracting the like terms we get

6y = -36

y = -6

Step 3: Solve for x

Plug in the value of in one of the equations

Let us solve for x in the first equation -4x -2y = -12

Plugging in the value of y = -6 in the above equation we get

-4x -2(-6) = -12

-4x +12 = -12

-4x = -24

x = 6

So ( 6, -6 ) is the solution to this system of equations.